2014
DOI: 10.1002/micr.22250
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors of free flap thrombosis in breast reconstruction surgery

Abstract: Vascular thrombosis is one of the major postoperative complications of free flap microvascular breast reconstruction operations. It is associated with higher morbidity, higher cost, increased length of hospital stay, and potentially flap loss. Our purpose is to evaluate the rate of this complication and whether patient characteristics play a role. Using the Nationwide Inpatient Sample (NIS) database, we examined the clinical data of patients who underwent free flap breast reconstruction between 2009 and 2010 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 25 publications
8
45
0
4
Order By: Relevance
“…Higher complication rates in this subgroup however are in line with other publications from the centers where SIEA flaps are not performed regularly 3335 and may be attributed to vessel caliber and flap thrombosis.…”
Section: Discussionsupporting
confidence: 89%
“…Higher complication rates in this subgroup however are in line with other publications from the centers where SIEA flaps are not performed regularly 3335 and may be attributed to vessel caliber and flap thrombosis.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Nakamizo et al reported that previous surgery and infection were the strongest risk factors for flap failure . Other fields outside of the head and neck literature have identified risk factors associated with flap failure such as peripheral vascular disease and thrombocythemia . Additionally, differences may exist when free flap reconstruction is performed within various subsites.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical studies do not completely agree on clearly defined risk factors for flap thrombosis and failure, [19][20][21][22][23][24] the influence of these variables in conjunction with tamoxifen therapy is not well studied and should be considered when assessing tamoxifen as a risk factor. In our study, the percentage of patients with preoperative radiation was significantly higher in the tamoxifen cohort, similar to prior studies, 7,8 as the majority of these patients underwent delayed reconstruction.…”
Section: Discussionmentioning
confidence: 98%
“…Large reviews provide conflicting conclusions on preoperative radiation therapy as an independent risk factor for flap thrombosis. 20,21,25 Radiation, however, is known to result in intimal and smooth muscle damage in vessels as well as cause perivascular fibrosis that can affect venous anastomosis patency. 26,27 Although the higher rate of preoperative radiation did not increase the incidence of arterial or venous thrombosis in the tamoxifen group, radiation damage to the recipient vasculature may have contributed to the difficulty in flap salvage and the higher rate of flap failure secondary to thrombosis in the tamoxifen cohort.…”
Section: Discussionmentioning
confidence: 99%